A Case Study on Relationship between Optical Path Length and Detection Limit of an NO Non-Dispersive Infrared Analyzer - Vuong Dinh, Trieu; Won Ahn, Ji; Young Choi, In; Chun Kim, Jo (International Journal of Engineering and Technology, 2018)
Non-dispersive Infrared (NDIR) analyzer has been wildly used to monitor the emission of air pollutants from stationary sources. Lower detection limit of an NDIR analyzer depends on the optical path length of the IR beam. The relationship between the path length and the detection limit of a NO NDIR analyzer was investigated in this work. The path lengths of the analyzer were varied as 4.8, 8, 10.4 and 16 m. The measurement range of NO gas was 0 ~ 200 ppm. Gold coated mirrors were used to produce multi pathways for the NDIR gas cell based on the White cell principle. It was found that the detection limit of NO was 1.0 ppm at 16 m of the pathlength. In contrast, that of NO was 4.28 ppm at 4.8 m of the path length. The lower detection limit was inversely proportional to the optical path length. The optimal path length for NO gas in the range of 0 ~ 200 ppm was 16m.Â Â